LOMBER DİSK HERNİLİ HASTALARDA ENDOTELİN-1 DÜZEYİ İLE PFİRRMANN GRADELEMESİ ARASINDAKİ İLİŞKİNİN ARAŞTIRILMASI - USLU, EMİNE YILDIRIM (Fırat Üniveristesi, 2023)
Bu çalışmanın amacı, serum Endotelin-1 (ET-1) düzeyi ile "intervertebral disk dejenerasyonu, lomber disk hernisi, faset eklem dejenerasyonu, vertebra end plate dejenerasyonu " patolojilerinin radyolojik ve klinik görünümleri arasındaki ilişkiyi araştırmaktır. Çalışmaya 18-50 yaş arası 50 hasta ve 50 sağlıklı gönüllü kontrol alındı. Hasta ve kontrol grubunun Serum Endotelin-1 düzeyleri ölçüldü. Hastaların ağrı düzeyi Vizüel Analog Skalası (VAS) ile, fonksiyonelliği Oswetry Disabilite İndeksi (ODI) ve Short Form-36 (Sf-36) ile değerlendirildi. Hastaların Lomber MRG'larında disk dejeneresyon düzeyleri (Pfirrmann), disk herniasyon düzeyleri (Macnab), faset eklem dejenerasyon düzeyleri ve end plate dejenerasyon düzeyleri (Modic) incelendi. ET-1 düzeyi hasta grubunda kontrollerden istatistiksel olarak anlamlı yüksek bulundu (p<0.05). ET-1 düzeyi ile intervertebral disk dejenerasyon derecesi, end plate dejenerasyon derecesi, faset eklem dejenerasyon derecesi arasında pozitif korelasyon izlendi. Lomber disk hernisi gradelemesi ile ET-1 düzeyi arasında ise korelasyon izlenmedi. Bu veri bize ET-1'in herniasyon sürecinden çok dejenerasyon süreciyle ilişkili olduğunu gösterdi. Radyolojik olarak da disk, faset ve end plate dejenerasyon dereceleri birbirleriyle korele bulunurken herni gradelemesiyle korele olmadıkları görüldü. Nörolojik defisiti olan ve olmayan hastalar arasında ET-1 düzeyleri arasında anlamlı fark gözlenmedi. Ayrıca VAS skoru, ODİ ve SF36 alt parametreleriyle ET-1 arasında da korelasyon izlenmedi. Bu bulgular bize serum ET-1düzeyinin klinik bulgular ve fonksiyonellikle ilişkili olmadığını düşündürdü. Çalışmamızdaki veriler ışığında ET-1'in bel ağrısı oluşturan mekanizmalarla yakından ilişkili olduğu söylenebilir. Verilerimiz disk dejenerasyon etyopatogenizinin aydınlanmasına katkıda bulunabilir. Çalışmamızda klinik bulgular ve fonksiyonellikle ET-1 arasında korelasyon izlenmemiş olması klinik parametrelerin değerlendirilmesinde ET-1'in bir belirteç olarak kullanılamayacağını gösterebilir. Anahtar Kelimeler: LDH, Endotelin-1, Pfirrmann, Macnab, Modic

INVESTIGATION OF THE RELATIONSHIP BETWEEN PFIRRMANN GRADING AND ENDOTHELIN-1 LEVEL IN PATIENTS WITH LUMBAR DISC HERNİA The aim of this study is to investigate the relationship between serum Endothelin-1 (ET-1) level and radiological and clinical manifestations of "intervertebral disc degeneration, lumbar disc herniation, facet joint degeneration, vertebral end plate degeneration" pathologies. Fifty patients aged 18-50 years and 50 healthy volunteers were included in the study. Serum Endothelin-1 levels of the patient and control groups were measured. The pain level of the patients was evaluated with the Visual Analogue Scale (VAS), and functionality was evaluated with the Oswestry Disability Index (ODI) and Short Form-36 (Sf-36). Disc degeneration levels (Pfirrmann), disc herniation levels (Macnab), facet joint degeneration levels and end plate degeneration levels (Modic) were examined in Lumbar MRIs of the patients. ET-1 level was found to be statistically significantly higher in the patient group than in the controls (p<0.05). A positive correlation was observed between the ET-1 level and the degree of intervertebral disc degeneration, the degree of end plate degeneration, and the degree of facet joint degeneration. No correlation was observed between lumbar disc herniation grading and ET-1 level. This data showed us that ET-1 is associated with the degeneration process rather than the herniation process. Radiologically, disc, facet and endplato degeneration grades were correlated with each other, but not with hernia grading. There was no significant difference in ET-1 levels between patients with and without neurological deficits. In addition, no correlation was observed between VAS score, ODI and SF36 sub-parameters and ET-1. These findings made us think that serum ET-1 level is not related to clinical findings and functionality. In the light of the data in our study, it can be said that ET-1 is closely related to the mechanisms that cause low back pain. Our data may contribute to elucidating the etiopathogenesis of disc degeneration. The fact that there was no correlation between clinical findings and functionality and ET-1 in our study may indicate that ET-1 cannot be used as a marker in the evaluation of clinical parameters. Keywords: LDH, Endothelin-1, Pfirrmann, Macnab, Modic
Investigation of the relationship between pfirrmann grading and endothelin-1 level in patients with lumbar disc hernia
Keywords: Fiziksel Tıp ve Rehabilitasyon